Evaluations of Michelle Obama as First Lady: The Role of Racial Resentment. Issue 2 (13th May 2016) - Knuckey, Jonathan; Kim, Myunghee
Abstract : The election of Barack Obama in 2008 was initially viewed as signaling a postracial era in American politics. However, since 2008, race and racial attitudes have appeared to pervade American political discourse and shape political attitudes and behavior to an even greater extent. Using data from the American National Election Studies, this article examines the extent to which white racial attitudes have shaped evaluations of perhaps the most visible African American in politics today after the president: the First Lady, Michelle Obama. Findings show that racial resentment played a large role in evaluations of Michelle Obama, even after controlling for other explanatory variables, which include partisanship, ideology, and affect toward Barack Obama.